New bedrock map of Dome C, Antarctica, and morphostructural interpretation of the area - Frédérique Rémy; Luisa Zuccoli; A. Bini; A. Forieri; Ignazio E. Tabacco; Achille Zirizzotti (Annals of Glaciology, 2004)
AbstractA new bedrock map of the Dome C area is presented, based on all radar data collected during Italian Antarctic Expeditions in 1995, 1997, 1999 and 2001. The map clearly distinguishes the Dome C plateau, along with valleys and ridges. The plateau develops at three different altimetric levels, and its morphology is characterized by hills and closed depressions. There are no visible features which can be ascribed to glacial erosion or deposition. The major valley is 15 km wide and 500 m deep; its axis is parallel to that of other valleys and ridges in the plateau. The valley bottom is not flat, but contains a saddle at its centre. The morphology of the major valley may be considered a relict one which was not modified by the overlying ice cap. Two large ridges, characterized by hills, saddles and depressions, lie near the boundaries of the area. The map is used to recalculate ice thickness below the European Project for Ice Coring in Antarctica (EPICA) borehole. The new thickness is 3300 m, 50m greater than before, implying that the expected palaeoclimate record from the ice core could extend back >800 kyr.